AS INITIO STUDYOF AMMONIA CLUSTERS: (NH3)n(n = 2-6) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Hydrogen bonded neutral clusters of ammonia, (NH3)n (n = 2-6), have been theoretically investigated employing the D95++(d,p) (and wherever necessary, higher) basis sets at the Hartree-Fock (HF) level as well as with second-order MflJller-Plesset(MP2) perturbation theory.'While the ammonia trimer and tetramer exhibit perfect molecular symmetries and are nonpolar, the pentamer and hexamer both optimize with slight deviations from perfect symmetries and are seen to posses marginal. but nonzero dipole moments. The (NH3)nlinear clusters are seen to be chemically softer than the correspondingcyclic ones.